New approaches for on-court endurance testing and conditioning in competitive tennis players - Baiget, E.; Iglesias, X.; Fuentes, J. P.; Rodriguez, F. A. (Strength and Conditioning Journal, 2019)
The control and quantification of internal and external training loads is essential to the correct design of training programs. In tennis, along with anaerobic, psychological, and tactical abilities, technical skills and endurance conditioning are key to competitive performance. Therefore, it could be useful to use testing and training loads and methods that include physiological and technical parameters at the same time. The aim of this review is to identify a new training load parameter, suitable for on-court use in tennis, based on technical and physiological skills, to allow control of internal and external loads.